2009
DOI: 10.3109/10837450902980262
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl methanesulphonate in a parenteral formulation of BMS-214662 mesylate, a selective farnesyltransferase inhibitor: Formation and rate of hydrolysis

Abstract: The objectives of the present study were to investigate the formation and rate of hydrolysis of ethyl methanesulphonate (EMS) in BMS-214662 mesylate drug substance and parenteral formulation by a gas chromatographic/mass spectrometric (GC/MS) method. EMS levels in the drug substance ranged between 0.3 microg/g and 0.8 microg/g. The parenteral formulation contains ethanol and the reaction between residual free methane sulphonic acid and ethanol may lead to the formation of EMS. Given that EMS is a potent mutage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…If such a reaction were feasible alkyl sulfonates would be formed in every case in which an alcoholic solvent was used in the synthesis of a sulfonic acid salt; this is disproved by the data on nelfinavir mesilate manufactured in a manner excluding any purging of MMS and EMS . In 2009, Nassar et al reported that, contrary to expectation, no EMS was generated following storage of a mesilate salt parenteral drug product (formulated at pH 4 in 30% aqueous ethanol) for 18 weeks at 25 °C or 6 weeks at 60 °C. A similar finding was reported by Ubben et al, who in 2011 stated, “Our analyses found that a mesylate will not form from a mesylate salt and an alcohol.” Thus, the salt-alcohol interaction hypothesis is considered mechanistically impossible, which is supported by experimental data.…”
Section: Technical Updatementioning
confidence: 99%
“…If such a reaction were feasible alkyl sulfonates would be formed in every case in which an alcoholic solvent was used in the synthesis of a sulfonic acid salt; this is disproved by the data on nelfinavir mesilate manufactured in a manner excluding any purging of MMS and EMS . In 2009, Nassar et al reported that, contrary to expectation, no EMS was generated following storage of a mesilate salt parenteral drug product (formulated at pH 4 in 30% aqueous ethanol) for 18 weeks at 25 °C or 6 weeks at 60 °C. A similar finding was reported by Ubben et al, who in 2011 stated, “Our analyses found that a mesylate will not form from a mesylate salt and an alcohol.” Thus, the salt-alcohol interaction hypothesis is considered mechanistically impossible, which is supported by experimental data.…”
Section: Technical Updatementioning
confidence: 99%